Qing China and the Legal Treatment of Mental Infirmity: A Preliminary Sketch in Tribute to Professor William C. Jones - William P. Alford; Chien-Chang Wu (Washington University Global Studies Law Review, 2003)
This short tribute to Professor Jones aspires toward the high standard he continues to set as it reports briefly on research being conducted into the legal treatment of madness in late imperial China. As the work of Michel Foucault, among others, has demonstrated, an inquiry into definitions, legal and otherwise, of insanity and the treatment thereof is revealing not only about its immediate subject matter, but as well for what it suggests about that which a society understands to be normal behavior. Notwithstanding the brilliant work by Arthur Kleinman on mental illness in Chinese society, and the alarming reports by Robin Munro on the abusive use of psychiatric confinement in the People’s Republic of China, there is, however, surprisingly little written, whether by Chinese or Western scholars, regarding the legal construction of insanity in China.
Keywords: Law; Translators (Persons); China